2019
DOI: 10.1001/jamafacial.2019.1090
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneity Assessment in Dually Innervated Gracilis Smile Reanimation Surgery

Abstract: IMPORTANCESurgeons have sought to optimize outcomes of smile reanimation surgery by combining inputs from nerve-to-masseter and cross-face nerve grafts. An objective assessment tool could help surgeons evaluate outcomes to determine the optimal neural sources for smile reanimation.OBJECTIVE To evaluate the use of a novel video time-stamping method and standard outcome measurement tools to assess outcomes of facial reanimation surgery using various innervation strategies. DESIGN, SETTING, AND PARTICIPANTSCohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 33 publications
0
49
0
Order By: Relevance
“…Faria et al [21] reported first contractions observed after 3-6 months, with an average of 3.7 months. This is in contrast to the CFNG, which can take up to two years for maximal results from the time of initial surgery [13] . Moreover, GFMT with masseteric nerve innervation can be done as a single-stage procedure, which is more ideal for patients with significant medical comorbidities and operative risk.…”
Section: Masseteric Nerve Transfermentioning
confidence: 94%
See 4 more Smart Citations
“…Faria et al [21] reported first contractions observed after 3-6 months, with an average of 3.7 months. This is in contrast to the CFNG, which can take up to two years for maximal results from the time of initial surgery [13] . Moreover, GFMT with masseteric nerve innervation can be done as a single-stage procedure, which is more ideal for patients with significant medical comorbidities and operative risk.…”
Section: Masseteric Nerve Transfermentioning
confidence: 94%
“…The nerve is then allowed to grow through the cable graft, and the second stage is performed when the regenerated axons have reached the distal end of the cable graft. The mean interval between the two stages of the operation typically ranges between 8 to 12 months in adults and 6 to 9 months in children [3,4,13] . This timeline depends on the rate of facial axonal regeneration through the nerve graft, which can be followed clinically using the progression of the Tinel sign through the length of the graft.…”
Section: Cross Facial Nerve Graftmentioning
confidence: 99%
See 3 more Smart Citations